Occupational hazard in urolithiasis patients in Qatar: a single-center cross-sectional study - Kamran Hassan Bhatti; Rawa Bapir; Nadeem Sohail; Faaz Salah Gomha; Ahmed H.A. Shaat; Aftab Ahmed Channa; Khalid Mohammed Abdelrahman; Bryar Othman Muhammed; Nali H. Hama; Fahmi H. Kakamad; Berun A. Abdalla; Jihad Ibrahim Hama; et al. (Archivio Italiano di Urologia e Andrologia, 2024)
Background: Urolithiasis is one of the most prevalent urological diseases and is associated with a substantial economic burden. Its prevalence varies according to geographical location. Qatar is a Middle Eastern country located in the Afro-Asian Stone Belt. It has a dry and hot climate, which may predispose individuals working in these environments to form kidney stones (KSs). Methods: A population sample of 4204 patients was categorized into five occupational classes. The frequencies and correlations of these occupations with KS formation were calculated. Results: Among the total cases, 2000 presented with KSs, with the majority being of Asian descent (49%), followed by individuals of Middle Eastern descent (35.1%). Technicians accounted for 35.15% of KS cases followed by clerks (29.2%) and executives (14.6%). Among KS cases, 44% had a single stone, 30% had multiple stones, and 26% had two stones. In comparing both KS and non-KS groups, age, gender, occupation, and race were significantly associated with KS formation (p-value < 0.05), while BMI did not show any significant correlation (p-value > 0.05). Asian males aged 31-40, working as technicians, were significantly more prone to urolithiasis. In comparing age, BMI, and gender with stone characteristics, only age was found significantly associated with stone size (p-value < 0.05). Occupation showed an impact on all studied stone characteristics. Clerks and technicians presented more frequently with stones within the 11-15 mm range, while executives more frequently presented with smaller stones (p-value < 0.001). Stone density was more frequently < 500 HU in workers, technicians and housewives and > 500 HU in executives and clerks (p-value < 0.001). Conclusions: Our findings revealed an elevated risk of urolithiasis among certain occupational groups, particularly technicians, who frequently work outdoors in high-temperature environments. Alternatively, the sedentary nature of clerical and executive positions can also contribute to the risk of urolithiasis.